2020
DOI: 10.1016/j.epsl.2020.116319
|View full text |Cite
|
Sign up to set email alerts
|

Neodymium isotope constraints on chemical weathering and past glacial activity in Svalbard

Abstract: Neodymium (Nd) isotopes in leached authigenic components of marine sediments have been increasingly used as a tracer of past ocean-water masses. Despite the general assumption that the Nd isotopic composition of solutes released during chemical weathering fingerprints the source rocks on continents, preferential dissolution of easily dissolvable phases may result in significant deviations in Nd isotopic composition between the solutes and the source rocks, with potential implications for the utility of Nd isot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
37
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 16 publications
(39 citation statements)
references
References 47 publications
2
37
0
Order By: Relevance
“…Iron oxides are also ubiquitous weathering products in soils, which can be transported as particulates in rivers prior to deposition as sediments (Bayon et al, 2004;Kraft et al, 2013). Recently, a study conducted in the Svalbard archipelago showed that the Fe oxide fractions leached from fjord sediments surrounding glaciated catchments composed of sedimentary rocks typically displayed Nd isotope signatures ( 143 Nd/ 144 Nd; or  Nd in epsilon notation) more radiogenic than corresponding detrital fractions (Jang et al, 2020). In agreement, Hindshaw et al (2018) reported similar differences in  Nd between both the easily dissolvable component of catchment rocks and their silicate residues, and dissolved and particulate riverine loads in Svalbard.…”
Section: Introductionmentioning
confidence: 82%
See 2 more Smart Citations
“…Iron oxides are also ubiquitous weathering products in soils, which can be transported as particulates in rivers prior to deposition as sediments (Bayon et al, 2004;Kraft et al, 2013). Recently, a study conducted in the Svalbard archipelago showed that the Fe oxide fractions leached from fjord sediments surrounding glaciated catchments composed of sedimentary rocks typically displayed Nd isotope signatures ( 143 Nd/ 144 Nd; or  Nd in epsilon notation) more radiogenic than corresponding detrital fractions (Jang et al, 2020). In agreement, Hindshaw et al (2018) reported similar differences in  Nd between both the easily dissolvable component of catchment rocks and their silicate residues, and dissolved and particulate riverine loads in Svalbard.…”
Section: Introductionmentioning
confidence: 82%
“…Despite this potential concern, several investigations have previously suggested that the sedimentary Fe-oxide fractions extracted from marine depositional settings receiving high inputs of river-borne material could still preserve a riverine  Nd signature (e.g. Bayon et al, 2004;Kraft et al, 2013;Jang et al, 2020).…”
Section: Potential Issues Related To the Influence Of Particle-seawater Interactionsmentioning
confidence: 99%
See 1 more Smart Citation
“…While Fe-Mn oxyhydroxide phases leached from bulk marine sediments are commonly used as paleoceanographic archives (e.g., Rutberg et al, 2000;Piotrowski et al, 2005;Gutjahr et al, 2008), the Fe-oxide fractions extracted from continental margin sediment records can also include pre-formed continental oxides associated with terrigenous material (e.g., Bayon et al, 2004;Kraft et al, 2013;Jang et al, 2020), hence complicating their use for reconstructing past ocean circulation. In this study, the evidence that leached Fe-oxyhydroxide phases significantly depart from NADW-like ε Nd values clearly point towards the presence of such pre-formed continental oxides.…”
Section: Core-top Evidence For a Seawater-derived Nd Isotopic Signature In Glauconitementioning
confidence: 99%
“…In this study, the evidence that leached Fe-oxyhydroxide phases significantly depart from NADW-like ε Nd values clearly point towards the presence of such pre-formed continental oxides. In fact, recent investigations have shown that river-borne Fe oxides are almost systematically characterised by more radiogenic Nd isotopic compositions relative to the associated detrital material (Hindshaw et al, 2018;Bayon et al, 2020;Jang et al, 2020). This Nd isotope decoupling between paired Fe oxide and detrital silicate fractions has been attributed to the preferential erosion and/or weathering of sedimentary rocks on continents (e.g., Bayon et al, 2020).…”
Section: Core-top Evidence For a Seawater-derived Nd Isotopic Signature In Glauconitementioning
confidence: 99%